The origins of midrash : from teaching to text - Mandel, Paul D., 1953- (Supplements to the Journal for the Study of Judaism, 2017)
In The Origins of Midrash : From Teaching to Text , Paul Mandel presents a comprehensive study of the words darash and midrash from the Bible until the early rabbinic periods (3rd century CE). In contrast to current understandings in which the words are identified with modes of analysis of the biblical text, Mandel claims that they refer to instruction in law and not to an interpretation of text. Mandel traces the use of these words as they are associated with the scribe ( sofer ), the doresh ha-torah in the Dead Sea scrolls, the "exegetes of the laws" in the writings of Josephus and the rabbinic "sage" ( ḥakham ), showing the development of the uses of midrash as a form of instruction throughout these periods.